Investigation on Mutual Contention Bandwidth Request Mechanisms in Two-Hop Relay Network with ITU-R Path Loss Models. (29th May 2013) - Anbazhagan, Rajesh; Rangaswamy, Nakkeeran
Abstract : The performance of two-hop contention based bandwidth request (BR) mechanism for WiMAX relay networks is investigated under ITU-R path loss models. In conventional WiMAX systems, the mobile stations (MS) update their contention window irrespective of their transmission failures. Those systems update their contention window on collision and due to channel error or unavailability of bandwidth. Further, these failure models have been suggested for single hop networks. The failure model in two-hop systems becomes complex since it may include additional failure events such as improper detection of codes and channel error due to varying path loss. Interestingly, these failure events (collision, channel error, unavailability of bandwidth, and improper detection of codes) do not occur evenly for both hops of a link. Hence, to set the contention window effectively, unique failure models are developed by considering the characteristics of BR mechanism and hop at which the BR is performed. In the proposed system, the two-hop BR is carried out with all combinations of message and code bandwidth request schemes. Among them, the message-code BR mechanism performs better under suburban fixed and outdoor to indoor or pedestrian environment, and code-code BR scheme performs better for vehicular environment.